SPDL1 overexpression was associated with poor prognosis and immune status in HCC through in vitro experiment and bioinformatics analysis - Ying-Ming Xu; Bo-Hua You; Ming Chen; Tian-Ping Xiong; Lin Shi; Qin Wei; Zhong-An Wang (Discover Oncology)
Abstract Background Numerous studies have established a strong link between the overexpression of spindle apparatus coiled-coil protein 1 (SPDL1) and cancer progression. However, the role of SPDL1 in hepatocellular carcinoma (HCC) remains unconfirmed. Methods The level of SPDL1 in HCC and its potential associations with prognosis and clinicopathological features were analyzed using TCGA and XENA databases. Bioinformatics and in vitro approaches were employed to investigate the biological functions, signaling pathways, and protein networks involving SPDL1. Additionally, correlation analyses were performed to explore the relationship between SPDL1 and the immune microenvironment. Results SPDL1 was overexpressed in HCC. Its overexpression correlated negatively with T stage, pathological stage, tumor status, age, body weight, differentiation, alpha-fetoprotein levels, vascular invasion, diagnosis, and poor prognosis in patients with HCC, positioning it as a risk factor for adverse outcomes. High-risk scores related to SPDL1 expression were significantly linked to poor prognosis in patients with HCC. Suppression of SPDL1 expression inhibited HCC cell proliferation, invasion, and migration. Furthermore, SPDL1 expression showed significant correlations with Th2 cells (r = 0.628), T helper cells (r = 0.296), Th17 cells (r = -0.422), neutrophils (r = -0.408), dendritic cells (r = -0.358), cytotoxic cells (r = -0.310), plasmacytoid dendritic cells (r = -0.275), and other immune cell populations in HCC. Conclusion Overexpression of SPDL1 is associated with poor prognosis and the immune microenvironment in HCC. Inhibition of SPDL1 expression can suppress tumor growth and metastasis, suggesting that SPDL1 may serve as a potential therapeutic target for HCC treatment.